Fungsi Temporer Kreatif pada Bangunan Terbengkalai: (Studi Kasus : Pameran Dian Lentera Budaya oleh Tisna Sanjaya) - Dwi Hatmojo Danurdoro; Yogie Candra Bhumi (Journal of Visual Art and Design, 2021)
Deterioration in urban areas requires revitalization efforts to reuse vacant buildings. This is essential because abandoned buildings are known to have a negative influence on the situation and public activities in their surroundings. To reduce negative impact and prevent further damage to such buildings, a first step that can be taken is to activate these spaces with a variety of temporary functions. Creative activities with their flexible and experimental character are ideal solutions for temporary use of abandoned buildings. Artists are considered capable of inspiring society, including policymakers, in responding to this issue. In addition, abandoned buildings can be seen as ‘spatial experiments’ that can be a good source of creative ideas for the city. This paper discusses an artist’s approach to creating works of art in response to a specific abandoned building. Furthermore, the realization of a temporary creative activity, its background, its initiation, and impact on the stakeholders and the community was studied as a possible model for a re-activation strategy towards abandoned buildings in urban areas involving various parties. The Dian Lentera Budaya exhibition by Tisna Sanjaya was used as a case study. The exhibition took place at Bioskop Dian, a historical building in the city of Bandung that is currently not in use.